2003
DOI: 10.1021/cm0258023
|View full text |Cite
|
Sign up to set email alerts
|

Triblock Copolymer Synthesis of Highly Ordered Large-Pore Periodic Mesoporous Organosilicas with the Aid of Inorganic Salts

Abstract: This communication describes the first preparation of highly ordered large-pore hexagonal periodic mesoporous organosilicas (PMOs) using triblock copolymer P123 as the template and inorganic salts as the auxiliary agents under strongly acidic conditions. The long-range structural order of the PMOs results from the enhanced self-assembly interaction imparted by inorganic salts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
135
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(149 citation statements)
references
References 48 publications
13
135
0
1
Order By: Relevance
“…39 This will benefit the interaction between the PEO corona and the hydrophobic organosilica oligomer. 17 Also, this competition for water with the ethylene oxide will lower the solubility of the Brij-76 surfactant and thus reduce the critical micelle concentration (CMC). The decrease in CMC favors the micelle-micelle interaction, and enhances the assembly ability of the micelles to help the formation of the ordered phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…39 This will benefit the interaction between the PEO corona and the hydrophobic organosilica oligomer. 17 Also, this competition for water with the ethylene oxide will lower the solubility of the Brij-76 surfactant and thus reduce the critical micelle concentration (CMC). The decrease in CMC favors the micelle-micelle interaction, and enhances the assembly ability of the micelles to help the formation of the ordered phase.…”
Section: Resultsmentioning
confidence: 99%
“…Highly ordered PMOs with 2D, 3D hexagonal and cubic Pm3n, Im3m, Fm3m mesophases can be synthesized under strongly basic or acidic conditions based on the electrostatic interaction between the organosilica and the template aggregates. 1,6,[14][15][16][17][18][19][20][21] However, because many organic groups are sensitive to acid or base and the breakage of Si-C bonds will possibly occur under such conditions, 22 …”
Section: Introductionmentioning
confidence: 99%
“…Guo et al found that the addition of a salt such as NaCl improves the degree of ordering of the materials. 37 More recently, they also reported that the addition of a large amount of K 2 SO 4 to a synthesis mixture containing BTME and pluronic F127 (EO 106 PO 70 EO 106 ) under acidic conditions affords a high quality cubic (Im 3 3m) ethane-silica mesophase with large cavities 9.8 nm in diameter. 38 Therefore, the most commonly studied typical organic linker group is the ethane group (-CH 2 -CH 2 -) because 1,2-bis(trialkoxysilyl)ethane is a widely available bridged organosilane precursor.…”
Section: Organic-bridged Periodic Mesoporous Organosilicasmentioning
confidence: 98%
“…KCl was added for the synthesis of ordered P123-SH n because the inorganic salt plays an important role for getting wellordered mesoporous ethane-silica using P123 as surfactant [16]. The sulfur contents increase irregularly as the concentration of MPTMS in the initial mixture increases (Table 1).…”
Section: Synthesis Of the Materialsmentioning
confidence: 99%